Multimodal-Based Technopreneurship Learning Model to Increase Entrepreneurial Creativity in Equality Education - Ilyas, Ilyas; Shofwan, Imam; Yusuf, Amin (Journal of Nonformal Education, 2025)
Background: Education plays a crucial role in improving a country’s economy, particularly through entrepreneurship education. With rapid technological advancements, the traditional entrepreneurship model has evolved into technopreneurship, which focuses on digitalization and industrial transformation. However, many educational institutions lack a clear and adequate understanding of this concept, necessitating effective learning methods that enable students to grasp and apply the principles of technopreneurialism. Research Objectives: This study aims to analyze the effectiveness of a multimodal-based learning model in technopreneurship education to enhance entrepreneurial creativity among equality education students. Research Method: The research employs a qualitative case study method. Data collection was carried out through observation, documentation, and interviews with 10 participants, consisting of students and teachers from an equality education school. Research Findings: The findings indicate that the multimodal-based learning model successfully created a more interactive, communicative, and active learning environment. In the context of technopreneurship, this model was shown to increase students’ confidence and communication skills, allowing them to engage in discussions and interact effectively. Research Conclusion: Multimodal-based learning effectively enhances students’ creativity and multimodal literacy, which has a positive impact on the innovation, development of ideas, and products with high commercial value. The curriculum for technology-based entrepreneurship education must continuously adapt to the needs of the business market to fully leverage this potential. Research Novelty: The novelty of this research lies in the application of a multimodal-based learning model within the specific context of technopreneurship education in equality schools. This study demonstrates that this method not only improves technological literacy but also significantly boosts students’ creativity and self-confidence in developing innovative business ideas.